Enhanced Oxygen Utilization Efficiency With Concomitant Activation of AMPK-TBC1D1 Signaling Nexus in Cyclophilin-D Conditional Knockout Mice - Radhakrishnan, Jeejabai; Baetiong, Alvin; Gazmuri, Raúl J. (Frontiers in Physiology, 2021)
We have previously reported in HEK 293T cells and in constitutive cyclophilin-D (Cyp-D) knock-out (KO) mice that Cyp-D ablation downregulates oxygen consumption (VO2) and triggers an adaptive response that manifest in higher exercise endurance with less VO2. This adaptive response involves a metabolic switch toward preferential utilization of glucose via AMPK-TBC1D1 signaling nexus. We now investigated whether a similar response could be triggered in mice after acute ablation of Cyp-D using conditional KO (CKO) mice by subjecting them to treadmill exercise involving five running sessions. At their first treadmill running session, CKO mice and controls had comparable VO2 (208.4±17.9 vs 209.1±16.8 ml/kg·min-1), VCO2 (183.6±17.2 vs 184.8±16.9 ml/kg·min-1), and RER (0.88±0.043 vs 0.88±0.042). With subsequent sessions, CKO mice displayed more prominent reduction in VO2 (genotype & session interaction p=0.000) with less prominent reduction in VCO2 resulting in significantly increased RER (genotype & session interaction p=0.013). The increase in RER was consistent with preferential utilization of glucose as respiratory substrate (4.6±0.8 vs 4.0± 0.9 mg/min, p=0.003). CKO mice also performed a significantly higher treadmill work for given VO2 expressed as a power/VO2 ratio (7.4±0.2 x 10-3 vs 6.7±0.2 10-3 ratio, p=0.025). Analysis of CKO skeletal muscle tissue after completion of five treadmill running sessions showed enhanced AMPK activation (0.669±0.06 vs 0.409±0.11 pAMPK/beta-tubulin ratio, p=0.005) and TBC1D1 inactivation (0.877±0.16 vs 0.565±0.09 pTBC1D1/beta-tubulin ratio, p<0.05) accompanied by increased glucose transporter-4 levels consistent with activation of the AMPK-TBC1D1 signaling nexus enabling increased glucose utilization. Taken together, our study demonstrates that like constitutive Cyp-D ablation, acute Cyp-D ablation also induces a state of increased O2 utilization efficiency, paving the way for exploring the use of pharmacological approach to elicit the same response, which could be beneficial under O2 limiting conditions.